A Study of the Correlation between Different Pairs of Physical and Mechanical Properties of Teak (Tectona Grandis) Grown in Various Localities of India and Burma - Mukerji, H. K. (Indian Forester, 1963)
The paper contains the results of correlation analysis showing the degree of inter- relations between Specific gravity, Maximum crushing stress and Rings per inch in natural and plantation grown teak (with and without eliminating the effects of extraneous factors) in order to study whether any one property can be predicted from a knowledge of other properties. It has been found that the effect of specific gravity on maximum crushing stress is predominant showing a reasonably high positive correlation between them, while the other character, rings per inch, plays an insignificant part. For some of the localities specific gravity can be used as a good indicator for predicting the maximum crushing stress with a fairly high degree of precision.